General practitioners’ decision-making strategies in the pharmacological treatment of musculoskeletal pain: A qualitative interview study - Nele Kornder; Victoria Jessica Hill; Sophia Naomi Groffebert; Annette Becker; Annika Viniol; Nicole Lindner (European Journal of General Practice)
Background Musculoskeletal pain is a leading reason for primary care visits and often requires pharmacological treatment. Despite rising prescription rates for non-opioid analgesics in Germany, little is known about GPs’ broader prescribing behaviour beyond opioid-related discussions. Understanding how GPs navigate pain management is key to supporting evidence-based prescribing.Objectives This study explored GPs’ decision-making strategies when prescribing for musculoskeletal pain and identified clinical challenges.Methods A qualitative study using semi-structured interviews was conducted with 15 GPs from Central and Northern Hesse, Germany. Participants were purposively recruited via a regional practice network. Interviews were analysed using Braun and Clarke’s thematic analysis, applying a combined deductive–inductive approach.Results Five major themes emerged: (1) prescribing approaches, (2) medication preferences, (3) doctor–patient relationship, (4) addressing psychosomatic factors, and (5) support needs. GPs preferred cautious prescribing, favouring metamizole and NSAIDs over opioids. Chronic pain was viewed as complex and required individualised, multimodal treatment and shared decision-making. Decision-making strategies were mainly shaped by guidelines like the WHO analgesic ladder and personal clinical experience; other guidelines were rarely mentioned. The doctor–patient relationship was considered essential, particularly in chronic pain contexts. Challenges included managing psychosomatic aspects and aligning treatment expectations.Conclusion GPs’ prescribing decisions are shaped by a combination of clinical judgement, patient dynamics, and systemic factors. The findings highlight the need for practical support tools that are integrated into daily workflows and emphasise shared decision-making, especially for chronic pain management. These insights can inform future interventions aimed at optimising prescribing practices in primary care.